'Monstrous' craft activism: A city yarn installation that wrought controversy through textile togetherness and community engagement. Issue 1 (1st March 2021) - Mandell, Hinda
Yarn has the potential to be monstrous when placed in public places. It can cause controversy, even when carefully planned as a public art installation involving collaboration with business developers and city stakeholders. This article focuses on the fallout from City Hall on one such yarn installation at a public park in Rochester, New York, in summer 2018 and applies the theoretical lens of 'monstrosity' used by Nicola Moffat in the book Textiles, Community and Controversy: The Knitting Map. The article demonstrates that while the twelve original tapestries were well received by the Rochester community, they were deemed 'not natural' by City Hall and ordered to be removed, despite permission previously granted by a city official. Ultimately, despite the handcraft controversy, this yarn installation ignited a positive community-based response in favour of public art and 'textile togetherness', a term defined in this article. And later the tapestries found a second life in a different community revitalization project. The article offers suggestions for future organizers of yarn installations and calls for more public art to be placed in urban areas as the output of community engagement.